The Concept of Employer and the Extension of the Subjective (Ratione Personae) Scope of Collective Labour Law - Hajn, Zbigniew (Acta Universitatis Lodziensis. Folia Iuridica, 2021)
In accordance with the changes in the provisions of the collective labour law in force since January 1, 2019, an employer within their meaning is also an organizational unit without civil law subjectivity, if it employs work contractors engaged in paid work engaged in paid work other than employees. This leads to the dualism of the notion and legal construction of the entity employing non-employee contractors on the basis of individual and collective relations. In individual legal relations, the entity employing contractors on the basis of civil law contracts may only be a civil law entity. On the other hand, in collective labour relations, organizational unit without civil law capacity may be regarded as their employer. The purpose of this study is to give the reasons for the thesis that such regulation leads to legal confusion, and the most appropriate way to remove it is to link the employer’s subjectivity with civil law subjectivity in individual and collective labour law.